MODEL "DIAMANT" OF INTERNAL COMMUNICATION ASSESSMENT IN EUROPEAN PROJECTS - Власенко, Олена Вікторівна; Гогунський, Віктор Дмитрович; Лукьянов, Дмитро Володимирович (Eastern-European Journal of Enterprise Technologies, 2013)
Dynamics of development and data updating in the field of project management are aimed to creation of new scientifically based approaches concerning projecting of communications in projects. Modern scientific researches and project management practice acquired certain forms of communications, which have found its wide representation in different standards and knowledge systems of project management. But application of traditional approaches on creation and implementation of communications, which were developed on principles of process presentation, is not enough for effective implementation of international projects, because known communication models represent elementary interaction acts of communicators rather than overall performance of communication system state. For the purpose of quality assessment of intercommunications, we chose model DIAMANT to be the subject of this article; this model represents in the best way all possible states of stakeholders when implementing communication act and meets every properties of Markov. The example of usage of this model for assessment of intercommunications in European project, which is currently implemented, is also given in this article. Proposed communication model with usage of additive chains of numbers may be helpful for project managers in the process of project managing in real-time mode to get quantitative results of assessment of intercommunications, which will give an opportunity to make forecasts concerning results of certain actions and increase chances for success in project implementation.